2017
DOI: 10.1016/j.jnutbio.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-dihydroxyvitamin D inhibits de novo fatty acid synthesis and lipid accumulation in metastatic breast cancer cells through down-regulation of pyruvate carboxylase

Abstract: Both increased de novo fatty acid synthesis and higher neutral lipid accumulation are a common phenotype observed in aggressive breast cancer cells, making lipid metabolism a promising target for breast cancer prevention. In the present studies we demonstrate a novel effect of the active metabolite of vitamin D, 1α,25-dihydroxyvitamin D (1,25(OH)2D) on lipid metabolism in malignant breast epithelial cells. Treatment of MCF10CA1a breast epithelial cells with 1,25(OH)2D (10 nM) for five and seven days decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Most studies believe that vitamin D prevents lipid accumulation. 12,36,37 In contrast, 1α,25(OH) 2 D 3 treatment increased lipid droplets and cholesterol levels in NRK-52E cells with normal glucose medium in current study. It was a novel finding and inspired us to explore the underlying mechanism.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Most studies believe that vitamin D prevents lipid accumulation. 12,36,37 In contrast, 1α,25(OH) 2 D 3 treatment increased lipid droplets and cholesterol levels in NRK-52E cells with normal glucose medium in current study. It was a novel finding and inspired us to explore the underlying mechanism.…”
Section: Discussioncontrasting
confidence: 56%
“…Meanwhile, the higher the concentration of 1α,25(OH) 2 D 3 was, the more significant the effect was. Most studies believe that vitamin D prevents lipid accumulation . In contrast, 1α,25(OH) 2 D 3 treatment increased lipid droplets and cholesterol levels in NRK‐52E cells with normal glucose medium in current study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that suppression of the DNL pathway is a potential target for inhibiting cancer cells , and thus, this study speculated that PMCTi might suppress the DNL pathway, which could lead to apoptosis induction in HepG2 cells. We investigated the inhibitory effect of 2.5 m m of the PMCTi for 24 h on the expression of ACLY, ACC, and FASN.…”
Section: Resultsmentioning
confidence: 89%
“…Previously, 1,25(OH) 2 D was shown to downregulate PC mRNA and protein expression in metastatic breast cancer cells [31]. PC is a mitochondrial enzyme facilitating the metabolism of pyruvate into OAA.…”
Section: Resultsmentioning
confidence: 99%